Skulduggery Pleasant Kindom Of The Wicked - Landy, Derek. (HarperCollins, 2007)
When twelve-year-old Stephanie inherits her weird uncle’s estate, she must join forces with Skulduggery Pleasant, a skeleton mage, to save the world from the Faceless Ones.